Investigation on polycarbonate surface wetting property with femtosecond laser irradiation and ultrasonic treatment. (July 2019) - Chen, Guojie; Wang, Z.K.; Zheng, H.Y.; Thwe, A.M.; Lam, Y.C.
Highlights: Fs laser irradiation achieved highly hydrophilic or super-hydrophobic surface. Controlling of water contact angle through controlling of laser energy deposition. Wettability was maintained under ultrasonic treatment in DI water and ethanol. Surface roughness may contribute to water contact angle. Different surface morphology can have similar water contact angle. Abstract: This study investigated the use of ultrashort femtosecond laser pulses to induce either hydrophilic or hydrophobic surfaces on polycarbonate (PC). It has been observed that controlled modification of wettability could be achieved over a wide range of water contact angle (WCA) from below 5° to above 150°. It has been shown that the pulse energy fluence and total energy deposition onto PC are the important factors in determining the laser-PC interaction, and therefore the different level of wettability on PC surface. XPS-spectra measurement indicates that the modification was caused dominantly by laser induced chemical bond changes. The changes in surface morphology may not noticeably contribute to the surface wettability. The stability investigation on the wetting property of laser modified surfaces has shown that ultrasonication in DI water or in ethanol led to decrease in hydrophobicity, and the decrease was more pronounced for super-hydrophobic surfaces. The level of hydrophilicity decreased as well for the laser induced hydrophilic surfaces. However, the change in hydrophobicity by post-treatment was not significant. The results would be useful in microfluidic chip design and fabrication with controlled surface wetting properties.